PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF BERBASIS DIGITAL DI ERA REVOLUSI INDUSTRI 4.0 SOCIETY 5.0 BAGI GURU SMPN 4 KOTA LANGSA - Amelia; Muliani, Fitra; Meutia, Rahmi; Nabilla, Ulya; Purnama Sari, Riezky; Nurviana; Fairus (Fakultas Teknik, Universitas Samudra, 2024)
Teachers are the key to the success of school digital initiatives in creating quality human resources. Teachers as educators are required to be proficient and skilled in using various ICT (Information and Communication Technology) based learning media. The sophistication of technology that can be utilized by teachers to improve the learning process experience is Artificial Intelligence (AI). Chat GPT is one of the implementations of the GPT model designed to interact with users in the form of conversation or chat. Based on the results of interviews with the Principal of SMPN 4 Kota Langsa, it is known that there are several problems, namely the lack of education for teachers related to AI, lack of knowledge in using AI, especially Chat GPT, and the absence of utilization of AI-based learning media. The method of implementing activities includes observation or field survey, socialization and counseling, training, mentoring and monitoring and evaluation. The questionnaire results generally show that the community service activities carried out at SMPN 4 Kota Langsa are said to have received sufficient participation from the teachers. The good response shown by the teachers helped the socialization process run smoothly, actively asking and answering questions so that the training process on the use of AI, especially Chat GPT, went well.